The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1471-2458-12-1085
|View full text |Cite
|
Sign up to set email alerts
|

Symptom load and functional status: results from the Ullensaker population study

Abstract: BackgroundThere is evidence to support that the number of self-reported symptoms is a strong predictor of health outcomes. In studies examining the link between symptoms and functional status, focus has traditionally been on individual symptoms or specific groups of symptoms. We aim to identify associations between the number of self-reported symptoms and functional status.MethodsA questionnaire was sent to people in seven age groups (N = 3227) in Ullensaker municipality in Southern Norway. The Standardised No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 27 publications
(34 reference statements)
7
55
0
Order By: Relevance
“…this is consistent with findings in a recent Norwegian study [24]. Previous research argues that a simple counting of symptoms, irrespective of type and severity, may contribute useful knowledge about functional status, in addition to the effect of individual health complaints [15]. We found that an increase in symptom burden was related to an increasing relative hazard of receiving a benefit, a result which supports that a similar approach also can be fruitful when investigating adolescent health and marginalization.…”
Section: Comparison With Previous Researchsupporting
confidence: 92%
See 1 more Smart Citation
“…this is consistent with findings in a recent Norwegian study [24]. Previous research argues that a simple counting of symptoms, irrespective of type and severity, may contribute useful knowledge about functional status, in addition to the effect of individual health complaints [15]. We found that an increase in symptom burden was related to an increasing relative hazard of receiving a benefit, a result which supports that a similar approach also can be fruitful when investigating adolescent health and marginalization.…”
Section: Comparison With Previous Researchsupporting
confidence: 92%
“…the results from this study are based on data from a comprehensive health survey of all 10th grade secondary school students (ages [15][16], living in six Norwegian counties during 1999-2004. the youth survey was initiated in Oslo and was subsequently extended to include five more counties in the following years. the survey included items about relationships with family, friends and school; physical and mental health; health behavior; and life events [16].…”
Section: Study Populationmentioning
confidence: 99%
“…However, Scandinavian population studies have shown widespread symptom reporting, especially by women, not related to disease. [4][5][6] CNCP patients have multiple symptoms but symptom intensity, bothersomeness and priority are not necessarily equivalents in patients with pain. 4,5,[7][8][9][10][11][12][13] Therefore, in the development of a HMS specifically to better understand the situation of CNCP patients in the clinic, the separate inclusion of items relating to symptoms, problems/bothersomeness and priorities is desirable.…”
mentioning
confidence: 98%
“…These researchers consider this to indicate that the complaints shared characteristics or common causal factors. Bruusgaard et al [276] also sent the NMQ and the Subjective Health Complaints Inventory to 7 elderly groups in Norway. The results showed a strong association between the number of symptoms and the functionality of the individuals.…”
Section: Population Groupsmentioning
confidence: 99%
“…Roquelaure et al (2012) [275] France Application of the NMQ in temporary workers. Bruusgaard et al (2012) [276] Norway Application of the NMQ in a population group. Ditchen et al (2013) [277] Germany Application of the NMQ in a varied occupational group.…”
Section: Authors Location Observationsmentioning
confidence: 99%